Unexpected linkage isomerism in chiral tetranuclear bis-tridentate (1,2,3-triazol-4-yl)-picolinamide (tzpa) grids - Gunnlaugsson, Thorfinnur (My University, 2019)
The synthesis of a chiral bis-tridentate (1,2,3-triazol-4-yl)-picolinamide (tzpa) ligand is described and its coordination chemistry with Cu(NO3)2 and [Cu(MeCN)4]PF6 is explored in the crystalline phase as well as in solution. Chiral [2 × 2] tetranuclear square grid complexes [Cu4(H21)4](NO3)8 and [Cu4(H1)4](PF6)4 were observed, and crystallographically analysed, these being linkage isomers with N4O2 and N5O coordination spheres, respectively. These come about by an unusual in situ amide deprotonation and coordination, which accompanies a CuI → CuII oxidation process.
Keywords: crystalline phase; oxidation process; linkage isomers